Nutritional Knowledge of Prospective Brides in Indonesia: A Systematic Review - Siregar, Mukhlidah Hanun (Universitas Al Azhar Indonesia, 2023)
One of the risk factors for stunting is the mother's lack of nutrition knowledge. Therefore, it is necessary to know how the knowledge of nutrition of the mother before getting married. This research method was a systematic review using the PRISMA-P guidelines and the PICOS criteria in various research articles on GARUDA. The results found only 3 articles that met the criteria with different definitions of nutritional knowledge. The average percentage of respondents with good nutritional knowledge is below 10%, meaning that out of 10 prospective brides only one has good nutritional knowledge. In Suscatin, guidance, and counseling related to health knowledge have been scheduled, but there needs to be an evaluation of the program that has been running.Keywords – Brides and grooms, Nutritional knowledge, Systematic review, Suscatin